Identification and structure of the nerve growth factor binding site on TrkA. - Robertson, A; Banfield, M; Allen, S; Dando, J; Mason, G; Tyler, S; Bennett, G; Brain, S; Clarke, A; Naylor, R; Wilcock, G; Brady, R; et al. (2001)
Nerve growth factor (NGF) is involved in the development and maintenance of the nervous system and has been implicated as a possible therapeutic target molecule in a number of neurodegenerative diseases, especially Alzheimer's disease. NGF binds with high affinity to the extracellular region of a tyrosine kinase receptor, TrkA, which comprises three leucine-rich motifs (LRMs), flanked by two cysteine-rich clusters, followed by two immunoglobulin-like (Ig-like) domains. We have expressed the second Ig-like domain as a recombinant protein in E. coli and demonstrate that NGF binds to this domain with similar affinity to the native receptor. This domain (TrkAIg(2)) has the ability to sequester NGF in vitro, preventing NGF-induced neurite outgrowth, and in vivo, inhibiting NGF-induced plasma extravasation. We also present the three-dimensional structure of the TrkAIg(2) domain in a new crystal form, refined to 2.0 A resolution.